NOS3 Polymorphisms Can Influence the Effect of Multicomponent Training on Blood Pressure, Nitrite Concentration and Physical Fitness in Prehypertensive and Hypertensive Older Adult Women - Trapé, Átila Alexandre; Rodrigues, Jhennyfer Aline Lima; Ferezin, Letícia Perticarrara; Ferrari, Gustavo Duarte; Lizzi, Elisangela Aparecida da Silva; Moraes, Vitor Nolasco de; Silva, Roberta Fernanda da; Zago, Anderson Saranz; Brazo-Sayavera, Javier; Bueno Júnior, Carlos Roberto (Frontiers in Physiology, 2021)
Associations of endothelial nitric oxide synthase (NOS3) polymorphisms with hypertension and response to exercise training in prehypertensive and hypertensive older adult women remain unclear. This study used a multicomponent program (various capacities and motor skills) in the physical training intervention and analyzed the influence of NOS3 polymorphisms [-786T>C, 894G>T (Glu298Asp), and intron 4b/a] on the response of blood pressure (BP), nitrite concentration, and physical fitness in older adult women. 52 participants aged between 50 and 80 years underwent body mass index, BP, and six-minute walk, elbow flexion, and sit and stand up tests to assess physical fitness. The duration of the intervention was 12 weeks, twice a week, on non-consecutive days, and each session lasted 90 minutes, maintaining an intensity of between 13 (moderate) and 15 (intense), controlled by the Subjective Effort Perception Scale. Plasma/blood samples were collected to assess nitrite concentration and genotyping. The statistical analysis included Fisher's exact test and linear mixed-effects models. A positive effect of the multicomponent training was observed with a similar response in both prehypertensive and hypertensive groups. However, carriers of different genotypes demonstrated different responses to training: the decreases in systolic and diastolic BP and increases in nitrite expected from the physical training were smaller in variant genotype when compared to ancestral genotype carriers, especially in the hypertensive group. Our results show that the benefits of a multicomponent training intervention seem to be genotype-dependent. It should be possible to consider genetic variants when selecting a health-related treatment intervention.